Assessing the genetic diversity of Panicum coloratum var. makarikariense using agro‐morphological traits and microsatellite‐based markers - Armando, Lorena; Tomas, Maria Andrea; Garayalde, Antonio Francisco; Carrera, Alicia Delia (2018)
Panicum coloratum var. makarikariense is a perennial C4 grass native to South Africa with relatively good forage production under limited‐resource conditions. Genetic characterisation and breeding efforts have been scant, thus limiting its use in cattle raising systems. The goal of the present study was to assess the genetic diversity of a collection of P. coloratum var. makarikariense using agro‐morphological traits and molecular markers, in comparison with one accession of var. coloratum and one population of Panicum bergii. Agro‐morphological variability between and within accessions of var. makarikariense in a common garden setting was observed, showing that there is still opportunity for selection. Some accessions performed better than the commercialised material in relation to potential forage production. A total of 117 ISSR bands and 48 SSR alleles allowed the detection of genetic variability between and within accessions. The presence of accession‐specific bands suggested distinctness and limited gene flow. The genetic variability encountered in the commercialised material suggested that it is a stabilised population which has not undergone a strong selection process. Low correlation between agro‐morphologic and molecular variability was observed indicating that both approaches provide complementary information. Both morphological and molecular markers reveal genetic differentiation between varieties and species. This study provides a set of new SSR markers available for diversity assessment and valuable information that can be applied directly in collection management for breeding and conservation programmes.